Due interviste a Massimo Fagioli - Fagioli, Massimo; Izzo, Paolo (Il sogno della farfalla, 2005)
These interviews with Massimo Fagioli were sparked off by the polemics related to the referendum abrogative of a number of articles of law 40 on assisted fertility which took place in Italy on 12th and 13th June 2005. The psychiatrist manifested his opposition to the law that sees an undue role of the state and Church in the private lives of citizens and demonstrates that, behind the principle invoked by the supporters of the law who believe that life begins at the moment of conception, there is a religious ideology that annuls the reality of transformations that take place during gestation and, in particular, at birth when psychic reality and therefore human life in its totality take off. Following on from some recent talks of his, Fagioli explores in greater depth the themes of the formation and development of mental reality, sexuality as the realization of human identity in the relationship between men and women, the necessity that political transformation needs to have a coherent thought on human reality at its basis.